Konsep Pandangan Islam yang Menjawab Keraguan Non-Muslim dalam Novel Isabella karya Maulana Muhammad Saeed Dehlvi - Meddyan Heriadi (Pascasarjana UIN Fatmawati Sukarno Bengkulu, 2023)
Abstract: Concepts of Islamic Views Answering Non-Muslim Doubts in Maulana Muhammad Saeed Dehlvi's Isabella Novel. Literary works actually affect the morale of the people. With literature humans learn to see, reflect, and express the good and bad aspects indirectly. In other words, we learn morals without having to learn moral material. Just look at a novel or short story. Fiction prose works like this must contain messages or lessons that the characters will pass through. Through this wisdom we have actually learned morals. We can draw messages in an event. Is not the story of the prophets and apostles are in the form of stories. The difference with fiction is the story of the prophet is real while fiction is imagination. The problem in this research is how is the Concept of Islamic Views Answering Non-Muslim Doubts in the Novel Isabella by Maulana Muhammad Saeed Dehlvi? The purpose of this study is to reveal extrinsic values, especially moral and religious values in this Isabella novel. In this study, researchers used qualitative methods. In this case the researcher tried to observe the messages and knowledge unearthed in the novel Issabela by Maulana Muhammad Saeed Dehlvi with extrinsic analysis. This analysis in particular explores the moral values and religious values in this work. Based on this research it can be concluded that: a). The essence of Islam is monotheism, which is to force God. For the love part of Islam, this is not ignored. However, the value of love should have a parameter or in other words proof. Proof of love for God has been answered through the concept of taqwa in Islam, namely carrying out all his commands and avoiding all his prohibitions. b). Islam criticizes the concept of abb (father) in other religions. Islam itself offers a much better concept of Rabb (Preserver). Where the preserver has infinite power, while the abb concept is only limited to father and son. c) This novel also criticizes the concept of sacrifice in the Non-Muslim religion. Where God sacrificed his innocent child to atone for the sins of mankind. While in the concept of monotheism do not know humans bear the sins of other creatures. d). In the Non-Muslim religion in this novel, he considers some prophets to be sinful creatures. However, this is precisely opposed in Islam. Where all the messengers of God are holy. e). A true forgiving who has high value if he forgives his enemies when he has the strength and opportunity to retaliate. This is what happened to the Prophet. He has a high level of forgiveness. Like after his victory in Mecca, he forgave all his enemies. Unlike the case with God that exists in Non-Muslim religion where he forgives in a critical position. f). The miracle of the Prophet can actually be seen in every generation until the end of the world. The miracle is the Koran where until now the challenge of 1400 years ago to emulate the great quality of the literature has not been matched by anyone. Furthermore, the miracle that still exists today is the accomplishment of the Messenger of Allah who shook the world that no one can match.